Fermi Large Area Telescope observations of Local Group galaxies: detection of M31 and search for M33 - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Allafort, A.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astronomy & Astrophysics, 2010)
Context. Cosmic rays (CRs) can be studied through the galaxy-wide gamma-ray emission that they generate when propagating in the interstellar medium. The comparison of the diffuse signals from different systems may inform us about the key parameters in CR acceleration and transport.
CRIS-Team WoS Importer:2020-01-15